Influence of Language Learning Strategies to the English Proficiency Test Performance of College Students - Cawagdan – Cuarto, Harieth; Rivera, Emelinda (JPAIR Multidisciplinary Research, 2018)
Learning of English as second and even foreign language has been stressed out in all levels of education. Thus, teachers and researchers have been focusing on describing externally observable behaviors of language learners, followed by attempts to label categorized strategic behaviors and link them to language proficiency. This descriptive correlational study aimed to describe the extent of learners’ use of the language learning strategies (LLS) and determine its relationship with the English proficiency test performance of college students (N=82). The Oxford’s Strategy Inventory Language Learning (SILL) and a standardized College English Proficiency Test were the main instruments of the study. Results showed that memory, metacognitive, cognitive, compensation, organizing and evaluation and affective learning strategies do not significantly affect students’ English proficiency test performance; whereas social learning strategies is a strong predictor of students’ English proficiency test performance. This research provides a basis for utilizing social learning strategies as an intervention for improving students’ English proficiency.
Keywords: English as a Second and Foreign Language; Language Learning Strategies; English proficiency; descriptive correlation; Philippines; Oxford’s Strategy Inventory Language Learning (SILL)